2023
DOI: 10.1063/5.0141512
|View full text |Cite
|
Sign up to set email alerts
|

Formation and evolution of coherent structures in 3D strongly turbulent magnetized plasmas

Abstract: We review the current literature on the formation of coherent structures (CoSs) in strongly turbulent 3D magnetized plasmas. CoSs [Current Sheets (CS), magnetic filaments, large amplitude magnetic disturbances, vortices, and shocklets] appear intermittently inside a turbulent plasma and are collectively the locus of magnetic energy transfer (dissipation) into particle kinetic energy, leading to heating and/or acceleration of the latter. CoSs and especially CSs are also evolving and fragmenting, becoming locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 186 publications
0
2
0
Order By: Relevance
“…These studies frequently concentrate on reconnection rates, dimensionality, and spectra, as well as on additional topics such as violations of flux freezing in turbulence with reconnection-related consequences. Also, it is reported that strong turbulence is generated by nonlinear coupling of large amplitude unstable plasma modes, by the explosive reorganization of large-scale magnetic fields [46]. In this article, main emphasis is on the formation of coherent structures and how the turbulence is excited in astrophysical and laboratory plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…These studies frequently concentrate on reconnection rates, dimensionality, and spectra, as well as on additional topics such as violations of flux freezing in turbulence with reconnection-related consequences. Also, it is reported that strong turbulence is generated by nonlinear coupling of large amplitude unstable plasma modes, by the explosive reorganization of large-scale magnetic fields [46]. In this article, main emphasis is on the formation of coherent structures and how the turbulence is excited in astrophysical and laboratory plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, developed MHD turbulence cannot be epitomized by a sum of linear plane waves (e.g. Matthaeus et al 2015;Vlahos & Isliker 2023), as is implicit to the quasilinear framework and to the numerical simulations of synthetic wave turbulence that seek to test it. One particular, key assumption that must be called into question is that of random phased fluctuations.…”
Section: Introductionmentioning
confidence: 99%